2004
DOI: 10.1016/j.elecom.2004.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerisation of 3,4-ethylenedioxythiophene in aqueous solutions

Abstract: The potentiostatic electrosynthesis of poly(3,4-ethylenedioxythiophene) (PEDOT) in aqueous media without addition to the solution of any kind of surfactant has been studied by electrochemical quartz crystal microbalance (EQCM) and by spectroelectrochemistry. These tandem techniques have given valuable new information about the electropolymerisation process, allowing us to relate absorbance-charge and frequency-charge relationships to: (i) oligomers generation and chain propagation, as far as the length leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 38 publications
2
54
1
7
Order By: Relevance
“…Electropolymerisation, carried out using the three electrochemical techniques, is shown in taking into account the studies in [25,26], where it was observed that overoxidation of PEDOT takes place at potentials higher than +1.1 V, and also that at potentials lower than 0.9…”
Section: Electrode Modification By Edot Polymerisationmentioning
confidence: 99%
“…Electropolymerisation, carried out using the three electrochemical techniques, is shown in taking into account the studies in [25,26], where it was observed that overoxidation of PEDOT takes place at potentials higher than +1.1 V, and also that at potentials lower than 0.9…”
Section: Electrode Modification By Edot Polymerisationmentioning
confidence: 99%
“…EQCM is used to study small changes in mass depending on the applied voltage. 37,38 In QCM-D measurements the frequency response reflects the viscoelastic properties, thickness and density of any mass coupled to the quartz crystal that will appear as a change in frequency (f) and dissipation (D) at various overtones. 39 electrochemistry module connected to a Q-Sense (E4) chamber and an Autolab PGSTAT 10 was used as the potentiostat setup.…”
Section: Figure 1 When a Thin Film Of Pedot-s:h (Left Panel) Is Submmentioning
confidence: 99%
“…Aqueous solutions were prepared using high-quality water (resistivity of 18.2 MΩ·cm, Milli-Q A10 system, Millipore). 5 Scanning Electron Microscopy (SEM) images were taken under high vacuum conditions with a JEOL JSM-6335F. Energy Dispersive X-Ray (EDX) spectra were recorded with the X-Ray spectrometer of a Scanning Electron Microscope JEOL JSM-6460LV.…”
Section: Methodsmentioning
confidence: 99%
“…Very different reaction mechanisms have been evaluated, providing insight into the reaction intermediates, the electrosynthesis of diverse materials or the behavior of a material towards a specific analyte [1][2][3]. In particular, UV-Visible-NIR and Raman spectroelectrochemistry have been proven to be very useful for studying the synthesis and for characterizing conducting polymers [4][5][6][7]. These types of polymers have been applied in different material science areas such as light emitting diodes, sensors and biosensors, solar cells or fuel cells [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%